2015
DOI: 10.1016/j.schres.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging in first degree relatives of schizophrenia and bipolar disorder patients

Abstract: Objectives White matter (WM) abnormalities are one of the most widely and consistently reported findings in schizophrenia (SZ) and bipolar disorder (BD). If these abnormalities are inherited determinants of illness, suitable to be classified as an endophenotype, relatives of patients must also have them at higher rate compared to the general population. In this review, we evaluate published diffusion tensor imaging (DTI) studies comparing first degree relatives of SZ and BD patients and healthy control subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 87 publications
(187 reference statements)
3
24
0
1
Order By: Relevance
“…20 Regarding the present finding of a patient-control difference in this region, current and previous cross-sectional DTI findings 50 in siblings may be suggestive of a WM intermediate phenotype.…”
Section: Findings In Siblingssupporting
confidence: 49%
“…20 Regarding the present finding of a patient-control difference in this region, current and previous cross-sectional DTI findings 50 in siblings may be suggestive of a WM intermediate phenotype.…”
Section: Findings In Siblingssupporting
confidence: 49%
“…Some studies found abnormalities in the superior longitudinal fasciculus, inferior longitudinal fasciculus, corpus callosum, right uncinate fasciculus, right inferior fronto-occipital fasciculus, right anterior limb of internal capsule, and thalamic radiation in both BD-P and BD-FDR [68•, 69], while two studies did not find any abnormalities in older relative groups compared with controls [70, 71]. A population-based study showed abnormalities in similar white matter tracts in adolescents with subthreshold bipolar symptoms [72].…”
Section: Resultsmentioning
confidence: 99%
“…A population-based study showed abnormalities in similar white matter tracts in adolescents with subthreshold bipolar symptoms [72]. These tracts connect regions implicated in the identification and regulation of emotion, attention, impulsivity, response inhibition, set shifting, and risk-taking [68•]. Decreased WM volume is highly associated with genetic risk and familiality in BD [7074].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CN subjects were recruited via print and electronic media, and noticeboards in universities and local communities. Sample ascertainment and separate clinical assessments for younger (15)(16)(17)(18)(19)(20)(21) and older (22)(23)(24)(25)(26)(27)(28)(29)(30) age categories are provided in Perich et al 36 and in Supplementary Information 1.1. We pooled data across both age cohorts unless there was a specific correlation between a brain network measure and an age-specific clinical variable in either group.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%